AN ANALYTICAL OVERVIEW OF THE EXPRESSIVE FUNCTION OF PHRASEOLOGICAL UNITS IN ARTHUR CONAN DOYLE'S LITERARY WORKS - Erkulova FeruzaMelikuziyevna,; Yuldasheva Komila Tulkinbayevna, (Ustozlar uchun, 2025)
Phraseological units, or idiomatic expressions, play a crucial role in enriching the language of literary texts, serving both as stylistic embellishments and as tools for deeper character and theme development. In the realm of detective fiction, few authors have mastered the use of language with as much finesse as Arthur Conan Doyle. Best known for his Sherlock Holmes series, Doyle integrates a wide array of phraseological units to enhance narrative dynamism, develop memorable characters, and immerse readers in the socio-cultural atmosphere of Victorian and Edwardian England.